2019
DOI: 10.6061/clinics/2019/e786
|View full text |Cite
|
Sign up to set email alerts
|

Caloric test and video head impulse test sensitivity as vestibular impairment predictors before cochlear implant surgery

Abstract: OBJECTIVES: Currently, cochlear implant procedures are becoming increasingly broad and have greatly expanded. Bilateral cochlear implants and cochlear implants are more frequently applied in children. Our hypothesis is that the video head impulse test may be more sensitive than the caloric test in detecting abnormal vestibular function before cochlear implant surgery. The objective of this study was to compare the video head impulse test and caloric test results of patients selected for cochlear i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 29 publications
2
6
0
Order By: Relevance
“…It is possible to observe and analyze different parameters of the v-HIT, however the average gain of the VOR is one of the variables that is classically chosen to decide the vestibular hypofunction side ( 10 12 ). In our data set we could confirm other authors' findings ( 17 , 21 , 23 ) with respect to sensitivity and specificity of the v-HIT gain compared to the caloric test as the golden standard: When using the cut-off value of v-HIT gain <0.8 to classify vestibular hypofunction, we found a PPV of 65%, a NPV of 76%, a sensitivity of 46% and a specificity of 87%, which is in line with the literature.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…It is possible to observe and analyze different parameters of the v-HIT, however the average gain of the VOR is one of the variables that is classically chosen to decide the vestibular hypofunction side ( 10 12 ). In our data set we could confirm other authors' findings ( 17 , 21 , 23 ) with respect to sensitivity and specificity of the v-HIT gain compared to the caloric test as the golden standard: When using the cut-off value of v-HIT gain <0.8 to classify vestibular hypofunction, we found a PPV of 65%, a NPV of 76%, a sensitivity of 46% and a specificity of 87%, which is in line with the literature.…”
Section: Discussionsupporting
confidence: 91%
“…We noticed a high specificity and moderate sensitivity of the v-HIT gain using the caloric testing as a reference. Similar outcomes were presented in previous studies when comparing both vestibular tests (17,21,23,29,30). However, the study of Aalling et al (29) showed a higher PPV of 90% compared with our PPV of 65%.…”
Section: Comparison With Other Studiessupporting
confidence: 90%
See 1 more Smart Citation
“…The caloric irrigation test is a long-established measurement technique that has been used in multiple studies to investigate the function of hSCC after cochlear implantation (9,42,60,61). It has been described frequently that cochlear implantation has a significant impact on the outcome of this functional test (15,55).…”
Section: Caloric Irrigation Testmentioning
confidence: 99%
“…Due to regularly performed vestibular diagnostics, it is possible to inform and consult in an optimized way regarding the risk of vestibular damage associated with cochlear implantation [50]. Furthermore, a vestibular test that reveals pathologic side differences may also support the decision of which side should be implanted [51].…”
Section: Assessment Of the Vestibular Diagnosticsmentioning
confidence: 99%